2016
DOI: 10.1186/s12885-016-2943-4
|View full text |Cite
|
Sign up to set email alerts
|

Increased Wnt5a in squamous cell lung carcinoma inhibits endothelial cell motility

Abstract: BackgroundAngiogenesis is important both in normal tissue function and disease and represents a key target in lung cancer (LC) therapy. Unfortunately, the two main subtypes of non-small-cell lung cancers (NSCLC) namely, adenocarcinoma (AC) and squamous cell carcinoma (SCC) respond differently to anti-angiogenic e.g. anti-vascular endothelial growth factor (VEGF)-A treatment with life-threatening side effects, often pulmonary hemorrhage in SCC. The mechanisms behind such adverse reactions are still largely unkn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…miR-27b mimic also partially reverses rSjP40induced up-regulation of PPARg expression in LX-2 cells. In addition, we found that rSjP40 and miR-27b regulate the luciferase activity of PPRE luciferase reporter because the activity of the PPRE responsive element can be activated by PPARg activation (25). miR-27b mimic did not suppress the lipid droplet storage in LX-2 cells induced by rSjP40 (data not shown).…”
Section: Discussionmentioning
confidence: 87%
“…miR-27b mimic also partially reverses rSjP40induced up-regulation of PPARg expression in LX-2 cells. In addition, we found that rSjP40 and miR-27b regulate the luciferase activity of PPRE luciferase reporter because the activity of the PPRE responsive element can be activated by PPARg activation (25). miR-27b mimic did not suppress the lipid droplet storage in LX-2 cells induced by rSjP40 (data not shown).…”
Section: Discussionmentioning
confidence: 87%
“…Mostly, if the canonical or beta-catenin-dependent Wnt pathway is up-regulated, PPAR gamma is down-regulated ( 27 29 ). Additionally, PPAR gamma is also a non-canonical Wnt pathway target and is involved in the regulation of blood vessel growth via a non-canonical Wnt5a-dependent mechanism ( 30 ). Interestingly, Wnt5a is also a strong pro-inflammatory molecule that has been reported as a potent activator of cigarette smoke-induced inflammatory cytokine expression ( 30 32 ) and is characteristically up-regulated in squamous cell carcinomas ( 30 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, PPAR gamma is also a non-canonical Wnt pathway target and is involved in the regulation of blood vessel growth via a non-canonical Wnt5a-dependent mechanism ( 30 ). Interestingly, Wnt5a is also a strong pro-inflammatory molecule that has been reported as a potent activator of cigarette smoke-induced inflammatory cytokine expression ( 30 32 ) and is characteristically up-regulated in squamous cell carcinomas ( 30 ). Cigarette smoke (CS) is also the initial trigger of macrophage activation ( 33 ) and macrophage polarization toward the classical M1 and the alternative M2 lineages ( 34 ).…”
Section: Introductionmentioning
confidence: 99%
“…Future studies could consider several different aspects that have been explored in this review. Firstly, distinct NSCLC subtypes, should be observed and tackled differently; for instance, considerable differences exist between the response of SCC and AC cell lines to targeted therapies due to differential activation of the Notch pathway or the higher microvessel density present in AC [106]. Notably, as mentioned in a previous section of this thesis, Notch receptors have been found to have a higher predictive value for AC and this finding should be taken into account in future studies.…”
Section: Discussionmentioning
confidence: 94%
“…In one study, Wnt5a expression was found in 61.95% of NSCLC cases analyzed; it was mostly correlated with SCC, male sex and shorter OS and it was also associated with vascular mimicry and microvessel density [105]. Wnt-5 can contribute to angiogenesis by increasing microvessel formation via downregulation of peroxisome proliferator-activated receptor-gamma (PPARγ) and upregulation of VEGF-A expression [106]. Additionally, the ligand can contribute to EMT by downregulating β -catenin levels and other attachment proteins in the AC cell line H1975 [107].…”
Section: Clinical Evidencementioning
confidence: 99%